THE INFLUENCE OF ACCRUAL-BASED ACCOUNTING IMPLEMENTATION AND HUMAN RESOURCE COMPETENCE ON THE QUALITY OF FINANCIAL REPORTS AT THE DEPARTMENT OF INDUSTRY AND TRADE OF LAMPUNG PROVINCE - Rachmawati Sara Puspitasari (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to examine and determine the effect of the independent variables of accrual-based accounting implementation and human resource competence on the dependent variable of the quality of financial reports, this research was conducted at the Industry and Trade Office of Lampung Province. The sampling technique used was purposive sampling technique with 683 populations and a sample of 102 respondents with the criteria for determining the sample in this study only took samples in the fields related to the head of the department, the head of the finance or accounting section, the head of the field and staff who knew finance. based on the results of R - Square which is 0.223 shows that the implementation of accrual - based accounting and human resource competence has the ability to explain the quality of financial reports by 22.3% while the remaining 77.7% can be explained by other factors. based on the results of the f test that the implementation of accrual-based accounting (X₁) and human resource competence (X₂) simultaneously affects the quality of financial reports (Y). The results of the t test show that the accrual-based accounting implementation variable (X₁) partially affects the quality of financial reports (Y) and the competence of human resources (X₂) partially affects the quality of financial statements.